Phenology of Caryocar brasiliense in the Brazilian cerrado region - Leite, Germano L. D.; Veloso, Ronnie Von dos S.; Zanuncio, Jose C.; Fernandes, Luiz Arnaldo; Almeida, Chrystian I. M. (Elsevier B.V., 2006)
The objective was to study the phenology of Caryocar brasiliense Camb. (Caryocaraceae), a type of fruit of the Brazilian cerrado, in three areas (cerrado, pasture and in the campus of the Federal University of Minas Gerais) of the municipality of Montes Claros, State of Minas Gerais, Brazil, during 3 years. The plants of C brasiliense presented linear growth with about 50 cm of height and 35 cm of crown width per year. Soils with loamy texture, dystrophic, rich in aluminum and with low pH favor the production of this species. C. brasiliense produced higher quantity of flowers in the middle third, followed by the apical and basal parts of the crown, while the fruit production was higher in the basal third, followed by the middle and apical parts of the canopy of this species. C brasiliense bloomed during the dry period and produced fruits in the rainy season. Its fruits presented about 6, 8 and 6 cm of width, length and height, respectively, and 160 g of gross weight. The extrativism without control has strong impact on the propagation of C brasiliense because only about 7.96 and 10.65% of plants up to 1.0 m height and 59.58 and 44.73% higher than 3.0 m (reproductive phase) was observed in the cerrado and pasture, respectively. This indicates that fruit collectors, practically, remove all fruits of this tree and thus they reduce, considerably, the propagation of C. brasiliense in the cerrado areas of Brazil. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: phenology; Caryocar brasiliense; conservation